Pre-Treatment of Vegetable Raw Materials (Sorghum Oryzoidum) for Use in Meat Analog Manufacture - Viorica Bulgaru; Natalia Netreba; Aliona Ghendov-Mosanu (Applied Sciences)
This study proposes to analyze the chemical composition and the hydration kinetics of soryz (Sorghum Oryzoidum) grains in water at different temperatures (20, 30, 40, 45, 50, and 60 °C). The analyzed soryz variety presented a starch content of over 70%, and protein of about 10%, with an important supply of amino acids and a good source of K, Mg, and Ca. The efficiency of the hydration process was studied by applying Peleg’s model, which predicted water absorption by soryz under the experimental conditions. With increasing temperature, the Peleg’s rate constant, K1, and capacity constant, K2, decreased from 251 to 239 min/% and 2.52 to 2.49%−1, respectively. Fick’s second law was used to calculate the diffusion coefficient values. These values increased linearly with the temperature increase from 20 to 50 °C, ranging from 0.65 × 10−11 to 1.54 × 10−11 m2/s. They decreased with the subsequent rise in the environmental temperature up to 60 °C, 1.49 × 10−11 m2/s. The activation energy of soryz grains was 23.86 kJ/mol. The Arrhenius equation satisfactorily described the temperature dependence of the diffusivity coefficient. The results regarding the hydration kinetics of the soryz grains obtained are decisive in preparing this cereal for further use in meat analog manufacture.